THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND ADOLESCENT GIRLS' READINESS TO FACE THEIR FIRST MENSTRUATION (MENARCHE): A LITERATURE STUDY - Devi Fani Arista; Nurlinawati; Riska Amalya Nasution (JURNAL KEPERAWATAN UNIVERSITAS JAMBI, 2021)
ABSTRAK Latar Belakang: Kemenkes RI mencatat umur kejadian menarche di Indonesia rata-rata terjadi pada umur 12 tahun 4 bulan dengan prevalensi 60%, usia 13 tahun 30%, dan sisanya di atas 13 tahun. Remaja putri perlu mendapatkan dukungan keluarga agar memiliki kesiapan yang baik saat menghadapi menarche. Informasi yang kurang tentang perawatan dapat menyebabkan infeksi saluran reproduksi yang dapat menimbulkan kemandulan. Tujuan: Diketahui hubungan dukungan keluarga terhadap kesiapan remaja putri menghadapi haid pertama (menarche). Metode: Studi literatur ini berupa literatur review, pencarian artikel menggunakan elektronik based seperti Google Scholar, Garuda, Semantic Scholar dan Researchgate. Kata kunci dalam bahasa Indonesia â€œdukungan orang tua dan remaja putriâ€ dan dalam bahasa Inggris â€œrole of parents dan menarcheâ€. Dilakukan hal tersebut untuk mendapatkan artikel yang sesuai dengan kriteria inklusi lalu dilakukan review artikel, kemudian didapatkan 10 artikel dari hasil screening. Hasil: Hasil analisis dari 10 artikel, didapatkan 9 artikel menunjukkan bahwa keluarga mendukung remaja putri menghadapi menarche dan 1 artikel menunjukkan kurangnya dukungan keluarga. Simpulan: Dari 10 artikel didapatkan bahwa terdapat hubungan yang signifikan antara dukungan keluarga terhadap kesiapan remaja putri menghadapi menarche. Kata Kunci: Dukungan Orang tua, Menarche, Remaja Putri, Role of Parents ABSTRACT Background: The Ministry of Health of the Republic of Indonesia noted that the incidence of menarche in Indonesia occurred on average at the age of 12 years 4 months with a prevalence of 60%, age 13 years 30%, and the remaining age above 13 years . Young women need to get family support in order to have good readiness when facing menarche. Insufficient information about treatment can lead to reproductive tract infections that lead to infertility. Objective: Relationship of family support to young women's readiness to face the first menstruation (menarche). Methods: This literature study is in the form of literature reviews, electronic search articles such as Google Scholar, Garuda, Semantic Scholar and Researchgate. The keywords in Indonesian are â€œsupport for parents and young womenâ€ and in English â€œrole of parents and menarcheâ€. Doing this to get articles that match the inclusion criteria and then review the articles. Obtained 10 articles from the screening results. Results: The results of the analysis of 10 articles, 9 articles obtained indicate that families support young women facing menarche and 1 article shows a lack of family support. Conclusion: From 10 articles, it was found that there is a significant relationship between family support and young women's readiness to face menarche. Keywords: Parental support, Menarche, Young Women, The Role of Parents